Tingkat Literasi Keuangan Masyarakat (Studi pada Ibu Rumah Tangga di Kecamatan Kota Waingapu) - Natalia Nona Umbu Robaka; Linda Rambu Kuba Yowi (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2021)
It is important for housewives to get adequate ﬁnancial literacy in order to be able to manage ﬁnances properly because housewives are in control of household ﬁnances. Inaccurate ﬁnancial planning and determination of funding sources causes poor ﬁnancial management and decision making for housewives. Apart from that, the data related to the level of ﬁnancial literacy of women in East Sumba District were not yet available. The purpose of this study was to analyze the level of ﬁnancial literacy of housewives in the District of Waingapu City. The population in this study were all housewives who live in the District of Waingapu City. The sample in this study were 150 respondents. Determination of the sample in this study using purposive sampling method. Type of data used in research are the primary data. By using a questionnaire, which is to give a set of questions or a written statement to the respondent to be answered. The data analysis technique in this study used two data analysis methods, namely quantitative descriptive analysis which describes in general the level of ﬁnancial literacy and the second method is the cross tabulation technique using the SPSS 16.0 application. The results showed that the level of ﬁnancial literacy of housewives in the District of Waingapu City in total was 95% which indicates that the level of ﬁnancial literacy of housewives was high. It shows that out of 150 housewives respondents in the District of Waingapu City, it is known that the level of ﬁnancial literacy of housewives is the highest percentage (80.7%) of 121 people, the level of ﬁnancial literacy is moderate with a percentage (16.7) of 25 people and the low ﬁnancial literacy with a percentage (2.7%) of 4 people. This research adds to the empirical evidence about the level of financial literacy in Indonesia.